Edukasi Kesehatan Organ Reproduksi Remaja Putri di Desa Keliling Benteng Ilir [Health Education on Female Adolescent Reproductive Organs in Keliling Benteng Ilir Village] - Suryati Suryati; Siti Maria Ulfa; Fika Aulia; Norsyifa Norsyifa (UKInstitute, 2026)
Adolescence is a transitional period from childhood to adulthood characterized by physical, psychological, and social changes. One of the most important aspects of this phase is the development of the reproductive system. A lack of adequate knowledge and appropriate attitudes toward reproductive health can lead to various problems, such as sexually transmitted infections, unintended pregnancies, and other health disorders resulting from unhealthy behaviors. This community service activity aimed to enhance adolescent girls’ knowledge and awareness of the importance of maintaining reproductive organ health. The activity was carried out in Keliling Benteng Ilir Village on October 5, 2025, as an implementation of the Tri Dharma of Higher Education in the field of community service. The target participants were 15 adolescent girls aged 12–18 years, selected through a purposive sampling technique. The implementation method consisted of three stages: preparation, implementation, and evaluation. The implementation stage involved interactive lectures, group discussions, and educational video screenings, supported by leaflets and posters as learning media. Evaluation was conducted using pre-test and post-test assessments to measure the participants’ improvement in knowledge. The results showed a significant increase in participants’ knowledge regarding the anatomy of the reproductive organs, personal hygiene during menstruation, and the prevention of reproductive tract infections. This program successfully improved adolescents’ awareness and positive attitudes toward maintaining reproductive health and is expected to be sustainably implemented in other areas. Abstrak. Remaja merupakan periode peralihan dari masa kanak-kanak menuju kedewasaan yang ditandai oleh perubahan fisik, psikis, dan sosial. Salah satu aspek penting pada fase ini adalah perkembangan sistem reproduksi. Kurangnya pengetahuan dan sikap yang tepat terhadap kesehatan reproduksi dapat menimbulkan berbagai masalah, seperti infeksi menular seksual, kehamilan tidak diinginkan, serta gangguan kesehatan akibat perilaku tidak sehat. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan kesadaran remaja putri tentang pentingnya menjaga kesehatan organ reproduksi. Kegiatan dilaksanakan di Desa Keliling Benteng Ilir pada tanggal 5 Oktober 2025 sebagai implementasi Tri Dharma Perguruan Tinggi di bidang pengabdian masyarakat. Sasaran kegiatan adalah 15 remaja putri berusia 12–18 tahun yang dipilih secara purposive. Metode pelaksanaan meliputi tahap persiapan, pelaksanaan, dan evaluasi. Tahap pelaksanaan dilakukan melalui ceramah interaktif, diskusi kelompok, dan pemutaran video edukatif dengan bantuan media leaflet dan poster. Evaluasi dilakukan menggunakan pre-test dan post-test untuk menilai peningkatan pengetahuan peserta. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada tingkat pengetahuan peserta mengenai anatomi organ reproduksi, kebersihan diri saat menstruasi, serta pencegahan infeksi saluran reproduksi. Program ini berhasil meningkatkan kesadaran dan sikap positif remaja terhadap pentingnya menjaga kesehatan reproduksi dan diharapkan dapat dilaksanakan secara berkelanjutan di wilayah lain.